Silicone Oil Reinjection without Macular Buckling for Treatment of Recurrent Myopic Macular Hole Retinal Detachment after Silicone Oil Removal - Hammouda Hamdy Ghoraba; Sameh Mohamed Elgouhary; Hosam Osman Mansour (Journal of Ophthalmology)
Purpose. To evaluate the efficacy of silicone oil (S.O) reinjection without macular buckling for treatment of recurrent myopic macular hole retinal detachment (MHRD) after silicone oil removal. Methods. A retrospective consecutive interventional study from medical reports on cases of myopic MHRD. Fifty-three eyes of 51 patients underwent silicone oil removal after successful repair of MHRD were reviewed. The main outcomes were the retinal status after silicone oil removal and management of recurrent cases. Results. The rate of recurrent RD (Re RD) after silicone oil removal was 11.3% (6 out of 53 eyes). One case refused any other interference. In the remaining 5 eyes, 4 eyes (80%) could be reattached by S.O re-injection and one eye (20%) developed Re RD after S.O re-injection. Range of followup after management of recurrence was 5–53 months (mean 18.7 months). Conclusions. This case series concluded that the risk factors for recurrent RD after silicone oil removal from cases of myopic MHRD were high myopia, open flat MH, and large posterior staphyloma. Revision of vitrectomy and S.O re-injection can reattach most of recurrent cases.